Микробиологическая оценка эффективности герметизма различных материалов, применяемых при резекции верхушки корня для пломбирования корневых каналов (Эндодонтия Today, 2020)
In vitro evaluation of Prevotella Intermedia, Enterococcus faecalis and Candida Albicans microorganisms leakage study was carried out using four extracted lower central incisor teeth that were obturated using ProRoot MTA, AH Plus and guttapercha filling materials. Outcome of the study showed superior effectiveness of ProRoot MTA sealing ability that proves the fact of using this material in Oral Surgery as a retrograde root canal filling material in apical surgery.